Audit of acute limb ischaemia in a paediatric intensive care unit - Mumba, Jesse Musokota (Department of Anaesthesia, 2016)
Objective:Iatrogenic acute limb ischaemia in paediatric patients is a well-recognised complication of vascular access. This retrospective review of a paediatric intensive care unit identified patients who developed iatrogenic acute limb ischaemia between January 2008 and July 2013. Methods: The medical records of inpatients diagnosed with acute limb ischaemia during the study period were reviewed. Patients with other causes of acute limb ischaemia were excluded. A descriptive analysis of demographics, primary diagnosis, type of vascular access used, affected anatomical region, clinical presentation, type of therapy, type of block, response to intervention used and outcomes was conducted. Results:A total of 28 patients presented with signs of acute limb ischaemia, of whom 28.6% were aged <30 days, 46.4 % were between one and 12 months and 25% were between one and five years old; 78.6% of the affected limbs were lower limbs. Four patients had resolution of ischaemia upon removal of the vascular access devices. 23 patients received various forms of pharmacological sympathectomy, in addition to conservative therapy. One patient had missing data on the type of sympathectomy that was done. The response to the sympathectomies was: 60.9% good, 8.7% moderate, 8.7% poor and in 21.7% no responses. Documented tissue loss related to the ischaemia occurred in six (21.4%) of the 28 patients. Conclusions: Iatrogenic acute limb ischaemia in children are usually managed without surgical intervention. Pharmacological sympathectomies lead to increased blood flow to the affected limb via vasodilatation of collateral vessels, with an added advantage of reducing ischemic pain. The improved blood flow is postulated to avoid and/or minimise the amount of tissue loss. Pharmacological sympathectomies may, thus, have a role to play in th e management of iatrogenic acute limb ischaemia in the paediatric population.